Fast and Convenient Synthesis of Amine-Terminated Polylactide as a Macroinitiator for ω-Benzyloxycarbonyl-L-Lysine-N-Carboxyanhydrides. (21st July 2011) - Ju, Mingjie; Gong, Feirong; Cheng, Shujun; Gao, Yun
Abstract : Amine-terminated poly (L-lactide) (NH2 -PLLA) with various chain lengths were successfully synthesized by sequential tert-butyl- N -(3-hydroxypropyl) carbamate initiated bulk ring-opening polymerization (ROP) of L-lactide (L-LA) in the presence of Stannous(II) 2-ethylhexanoate (Sn(Oct)2 ) and deprotection of the N - tert -butoxycarbonyl (Boc) group at the end of the polymer chain. The polymers obtained were characterized by FT-IR, 1 H NMR, and GPC method. NH2 -PLLA thus prepared was used to initiate the polymerization of ω -benzyloxycarbonyl-L-lysine- N -carboxyanhydride (Lys (Z)-NCA), and the result confirmed the high nucleophilicity of the terminal amine group. This method was not only suitable for the preparation of low molecular weight NH2 -PLLA, but also quite efficient in the synthesis of high molecular weight samples.